2017
DOI: 10.1021/acs.inorgchem.7b01693
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Iridium(III) Complexes Based on a Pyrazole-Appended Quinoline-Based BODIPY

Abstract: A pyrazole-appended quinoline-based 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (L1, BODIPY) has been synthesized and used as a ligand for the preparation of iridium(III) complexes [Ir(phpy)(L1)]PF (1; phpy = 2-phenylpyridine) and [(η-CMe)Ir(L1)Cl]PF (2). The ligand L1 and complexes 1 and 2 have been meticulously characterized by elemental analyses and spectral studies (IR, electrospray ionization mass spectrometry, H andC NMR, UV/vis, fluorescence) and their structures explicitly authenticated by single-crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 108 publications
2
24
0
Order By: Relevance
“…The electronic absorption spectrum for [(C6) 2 Ir­(dppz)] + PF 6 – was measured in DMF solution at room temperature, as depicted in Figure . Like other C6-based iridium complexes reported previously, the complex exhibits notably intense absorption in the visible region, with ε = 9.8 × 10 4 M –1 cm –1 at λ = 485 nm and discernible absorption out to λ ∼ 540 nm, which is assigned to the C6-centered intraligand charge transfer (ILCT) along with weaker MLCT-based transitions. It is heartening that the ε value is 5 times more than that of a frequently used photoactive species, Ru­(bpy) 3 2+ , at 450 nm (ε = 1.8 × 10 4 M –1 cm –1 ), indicating viable candidates for the photoactive material.…”
Section: Results and Discussionsupporting
confidence: 70%
“…The electronic absorption spectrum for [(C6) 2 Ir­(dppz)] + PF 6 – was measured in DMF solution at room temperature, as depicted in Figure . Like other C6-based iridium complexes reported previously, the complex exhibits notably intense absorption in the visible region, with ε = 9.8 × 10 4 M –1 cm –1 at λ = 485 nm and discernible absorption out to λ ∼ 540 nm, which is assigned to the C6-centered intraligand charge transfer (ILCT) along with weaker MLCT-based transitions. It is heartening that the ε value is 5 times more than that of a frequently used photoactive species, Ru­(bpy) 3 2+ , at 450 nm (ε = 1.8 × 10 4 M –1 cm –1 ), indicating viable candidates for the photoactive material.…”
Section: Results and Discussionsupporting
confidence: 70%
“…Selected geometrical parameters are given in Table S2, while pertinent views along with atom numbering scheme are depicted in Figure . From the structure it is evident that in these complexes N5 and N6 from 2-phenylpyridine are trans -disposed (Figure ). Crystal structure further revealed that [(ppy) 2 Ir] unit in theses complexes is coordinated with N^N-chelating site of the terpyridine moiety creating a slightly distorted octahedral environment about Ir­(III) center.…”
Section: Resultsmentioning
confidence: 99%
“…In current medicinal chemistry, the incorporation of a pyrazole nucleus is a common practice to develop new drug-like molecules with anti-cancer, anti-diabetic, anti-viral, anti-inflammatory, anti-bacterial, anti-fungal, antineurodegenerative, anti-tubercular, anthelmintic, antimalarial, and photosensitizing properties [2][3][4][5][6][7][8][9][10], among others, thus giving rise to a great number of approved therapeutics [11]. Besides numerous biological activities, pyrazoles have also been documented to possess dyeing and fluorescence properties [12][13][14][15][16], and some of them can be used as colorimetric or fluorescent probes for sensing small molecules, ions, or pH [17][18][19][20][21][22][23][24][25][26][27][28], which may have applications in in vivo imaging [29][30][31]. Pyrazolopyridines are among the most studied condensed pyrazole systems in organic and pharmaceutical chemistry (Figure 1).…”
Section: Introductionmentioning
confidence: 99%